Histamine Modulates Midbrain Dopamine Neuron Differentiation Through the Regulation of Epigenetic Marks - Vargas-Romero, Fernanda; González-Barrios, Rodrigo; Guerra-Calderas, Lissania; Escobedo-Avila, Itzel; Cortés-Pérez, Daniel; López-Ornelas, Adolfo; Rocha, Luisa; Soto-Reyes, Ernesto; Velasco, Iván (Frontiers in Cellular Neuroscience, 2019)
During midbrain development, dopamine neuron differentiation occurs before birth. Epigenetic processes such as DNA methylation and demethylation as well as post-translational modification of histones occur during neurogenesis. Here we administered histamine (HA) into the brain of E12 embryos in vivo and observed significant lower immunoreactivity of Lmx1a+ and Tyrosine Hydroxylase (TH)+ cells, with parallel decreases in the expression of early (Lmx1a, Msx1) and late (Th) midbrain dopaminergic (mDA) genes. With MEDIP assays we found that HA decreases the percentage of 5-methylcytosine of Pitx3 and Th, without changes in 5-hydroxymethylcitosine. Additionally, HA treatment caused a significant increase in the repressive epigenetic modifications H3K9me3 in Pitx3 and Th, and also more H3K27me3 marks in Th. Furthermore, HA has a long-term effect on the formation of the nigrostriatal and mesolimbic/mesocortical pathways, since it causes a significant decrease in midbrain TH immunoreactivity, as well as alterations in dopaminergic neuronal fibers, and significant lower TH-positive area in the forebrain in whole-mount stainings. These findings suggest that HA diminishes dopaminergic gene transcription by altering several epigenetic components related to DNA and histone modifications, which affects mDA neuron progression during development.